Superselective Transarterial Chemoembolization for Unresectable or “Ablation Unsuitable” Hepatocellular Carcinoma in the Caudate Lobe: A Real World, Single-Center Retrospective Study - Yan, Liangliang; Ren, Yanqiao; Qian, Kun; Kan, Xuefeng; Zhang, Hongsen; Chen, Lei; Liang, Bin; Zheng, Chuansheng (Frontiers in Oncology, 2021)
Objectives: To analyze the clinical outcomes of Transarterial chemoembolization (TACE) for unresectable or “ablation unsuitable” hepatocellular carcinoma (HCC) in the caudate lobe (CL) found at initial presentation in clinical practice. Methods: Fifty-eight patients with HCC-CL undergoing conventional TACE from January 2015 to January 2020 were enrolled in our medical center. Overall survival (OS), progression-free survival (PFS), tumor response rate and major complication rates were analyzed. Multivariate analyses for potential clinical and radiologic factors were performed by using the Cox proportional hazard model. Results: The median OS was 23 months (95%CI: 18.1-27.9), and the median PFS was 11 months (95%CI: 7.4-14.6). The 1-, 3-, and 5-years OS rates were 66.5%, 31.9% and 15.7%, respectively. The 0.5, 1-, and 3-years PFS rates were 60.3%, 44.5% and 6.3%, respectively. Objective response rate was 53.4% and disease control rate was 79.3%. The most serious complication was bile duct injury, with an incidence of 3.4%. Multivariable analysis revealed that total bilirubin, Barcelona Clinic Liver Cancer stage, nonselective chemoembolization and TACE session were four significant factors associated with OS. Conclusions: Superselective TACE treatment might be associated with better survival benefits in unresectable or “ablation unsuitable” HCC in the CL without macroscopic vascular invasion (MVI) and adequate liver function, compared with the non-selective TACE group, and should be considered as an important reliable therapy for surgeons and interventional radiologists.